2021
DOI: 10.1016/j.jtumed.2021.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of an Origanum vulgare based dental gel with antimicrobial activity

Abstract: Objectives This study aims to formulate a new Origanum vulgare anti-caries dental gel with high antimicrobial activity. Methods O. vulgare essential oil was extracted using hydro-distillation, ethanol extraction, gas chromatography/mass spectrometry, and high-performance liquid chromatography methods. Antimicrobial activity of the produced gels with oregano oil and extract was determined through the disco-diffusion method. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Since the effect of the extract on planktonic growth of the dental plaque isolates were found to be only limited in this concentration range, we focussed on the anti-biofilm potential instead. Previous studies have already demonstrated the anti-biofilm potential of O. vulgare extracts against oral bacteria in standard in vitro setups ( Khan et al, 2017 ; de Oliveira Carvalho et al, 2020 ; Badekova et al, 2021 ). For example, Vaca et al (2021) showed that biofilms formed by a mixed culture of Str.…”
Section: Discussionmentioning
confidence: 99%
“…Since the effect of the extract on planktonic growth of the dental plaque isolates were found to be only limited in this concentration range, we focussed on the anti-biofilm potential instead. Previous studies have already demonstrated the anti-biofilm potential of O. vulgare extracts against oral bacteria in standard in vitro setups ( Khan et al, 2017 ; de Oliveira Carvalho et al, 2020 ; Badekova et al, 2021 ). For example, Vaca et al (2021) showed that biofilms formed by a mixed culture of Str.…”
Section: Discussionmentioning
confidence: 99%
“…[ ] Lithuania: 1.9 % (1) [Badekova, 2021] Morocco: 1.9% (1) [Moukhfi, 2022] Moldavia: 1.9% (1) Whole plant: 1.9% (1) [Drinic, 2020] Thailand: 1.9% (1) Total: 100% (53) Total: 100% (53) Total: 100% (52)…”
Section: Rosmarinus Officinalismentioning
confidence: 99%
“…[ Stanojevic, 2016] 220 °C: 22.3% (2) [Özer et al, 2018; 3 hours: 56.0% (28) [Atazhanova, 2022;Badawy, 2014;Badekova, 2021;Béjaoui, 2013;Brito, 2021;Giuliani, 2013;Khan, 2018;Khan, 2019;La Pergola, 2017;Licata, 2015;Mancini, 2014;Moghrovyan, 2019;Morshedloo, 2017;Moukhfi, 2022;Napoli, 2020;Stanojevic, 2016;Tanasescu, 2019;Teixeira, 2013;Tsoumani, 2022;Tuttolomondo, 2016;Zinno, 2023] 90 °C: 11.1% (1) [Sharififard, 2018] 1/1: 7.1%…”
Section: Chemical Constituents Of Essential Oilsmentioning
confidence: 99%
“…The gel components were selected based on their known functional roles in topical formulations, including viscosity modification, pH adjustment, flavor masking and preservative effects. Their quantities were optimized to achieve the desired consistency and properties in the final gel formulation [16], [17, ][18].…”
Section: Formulation Of Antibacterial Oral Gelmentioning
confidence: 99%

Natural antibacterial gel to fight tooth decay: An in-silico modeling approach

Appalaraju Dangeti,
V Venkata Trinadha Anand Kumar Reddy Jeeri,
Prakash Nathaniel Kumar Sarella
et al. 2023
World J. Bio. Pharm. Health Sci.